Helicobacter pylori: Novel Therapies - Eric Drouin (Canadian Journal of Gastroenterology)
The ideal therapy for Helicobacter pylori would cure the infection without resulting in the development of antibiotic resistance. Current therapies have variable cure rates; the reasons for treatment failure include bacterial resistance and poor compliance. Some antibiotics, such as furazolidone, may be affordable agents to treat this infection worldwide. New proton pump inhibitors, such as rabeprazole, can potentiate antibiotics. Nutriceuticals and probiotics demonstrate interesting in vitro activity against H pylori. Children rarely have symptoms to this infection and, therefore, are a suitable group in which to assess different nonaggressive therapies.